2012
DOI: 10.1039/c2ob26084k
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic asymmetric syntheses of inthomycins A, B and C

Abstract: The total syntheses of (+)-inthomycin A, (+)-inthomycin B and (-)-inthomycin C, the oxazole-triene antibiotics isolated from Streptomyces sp., have been accomplished via the highly enantio- and stereoselective construction of the C1-C7 (iododienyl)aldol units by taking advantage of a Cinchona alkaloid-catalyzed asymmetric β-lactone synthesis and their isomerisation-free Stille coupling with (E)-5-(3-(tributylstannyl)allyl)oxazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 48 publications
7
50
1
Order By: Relevance
“…[25] After extensive experimentation we found that the use of palladium(II)a cetate and triphenylphosphine in the presenceo f 1 m aqueouss odium bicarbonate allowed the union of the dienylboronic ester 15 with the (Z)-alkenyl iodide (Z)-17 to proceed with complete stereochemical fidelity to give the correspondingc oupled product 19 in 64 %y ield. Double deprotection of the triene 19 with HF in acetonitrile [9] gave the alcohol 20 which wasc onverted into inthomycin B 2 via aminolysis of the corresponding pentaflurorophenyl ester 21.O ur synthetic For the synthesis of inthomycin C 3,t he Suzukic oupling between the (Z,Z)-dienyl boronate 15 and the (E)-alkenyl iodide (E)-17 required furthero ptimization. Ultimately,w ef ound that the concentration of aqueous base proved crucial with the use of 0.25 m sodium bicarbonate giving the coupled product 22 in 65 %y ield.…”
mentioning
confidence: 99%
“…[25] After extensive experimentation we found that the use of palladium(II)a cetate and triphenylphosphine in the presenceo f 1 m aqueouss odium bicarbonate allowed the union of the dienylboronic ester 15 with the (Z)-alkenyl iodide (Z)-17 to proceed with complete stereochemical fidelity to give the correspondingc oupled product 19 in 64 %y ield. Double deprotection of the triene 19 with HF in acetonitrile [9] gave the alcohol 20 which wasc onverted into inthomycin B 2 via aminolysis of the corresponding pentaflurorophenyl ester 21.O ur synthetic For the synthesis of inthomycin C 3,t he Suzukic oupling between the (Z,Z)-dienyl boronate 15 and the (E)-alkenyl iodide (E)-17 required furthero ptimization. Ultimately,w ef ound that the concentration of aqueous base proved crucial with the use of 0.25 m sodium bicarbonate giving the coupled product 22 in 65 %y ield.…”
mentioning
confidence: 99%
“…In addition to the total syntheses presented in this review, we also achieved the syntheses of a variety of biologically active natural products with structural challenges such as febrifugine, 114) viridiofungin A, 115) trachyspic acid, 116) cinatrin C 1 , 117) β-erythroidine, 118) NW-G01, 119) inthomycins A-C, 120) englerin A, 121) ophiodilactones A and B, 122) and marinomycin A. 123) The strategies and methodologies we have developed are of great potential value in synthetic organic chemistry as well as pharmaceutical research.…”
Section: Resultsmentioning
confidence: 99%
“…The most common framework is the oxazole-triene-amide 18 also known as inthomycin derivative. 19 Inthomycin A (16; Fig. 2) with (4Z,6Z,8E)-congurated triene is present in the structures of oxazolomycin A, oxazolomycin A2, neooxazolomycin, 16-methyloxazolomycin, curromycin A, curromycin B, KSM-2690 B and in the both segments of bisoxazolomycin.…”
Section: Structural Classication Of Oxazolomycinsmentioning
confidence: 99%